Kritik Argumentasi Ingkar Sunah Menurut Al-Būṭī - Fatihunnada Fatihunnada; Afni Miftah Khoirunnisak (Refleksi, 2020)
This paper discusses the refutation of al-Būṭī to four arguments of some Sunnah’s refuter groups by examining the perspective of al-Būṭī’s thoughts in text and context in criticizing the Sunnah’s refuter. The method of critical analysis is the main part of this research to uncover al-Būṭī’s point of view in criticizing the Sunnah’s refuter in his work titled Yughāliṭūnaka idh Yaqūlūna as a primary source. The findings of this study are that al-Būṭī uses a text approach to argue the argument of the Sunnah’s refutation on the issue of Sunah authority compared to the Qur’an and the humanitarian aspects of a Prophet. al-Būṭī also use the historical approaches and scientific context in criticizing the Sunnah’s refuter argumentation on the problem of hadith forgery phenomena and the contradiction of ḥadīth with the findings of modern science. This shows that al-Būṭī’s criticism of the Sunnah’s refutation argument is present in a form that is in line with the thoughts of the Sunnah’s refutation itself. Al-Būṭī has tried to follow the Sunnah’s refuter’s way of thinking in contesting the authority of the Sunnah to find weaknesses in the Sunnah’s refuter’s way of thinking itself.